Isolation of Novel Microalgae from Acid Mine Drainage and Its Potential Application for Biodiesel Production - Yun, Hyun-Shik; Lee, Hongkyun; Park, Young-Tae; Ji, Min-Kyu; Kabra, Akhil N.; Jeon, Chung; Jeon, Byong-Hun; Choi, Jaeyoung (SPRINGER, 2014)
Microalgae were selected and isolated from acid mine drainage in order to find microalgae species which could be cultivated in low pH condition. In the present investigation, 30 microalgae were isolated from ten locations of acid mine drainage in South Korea. Four microalgae were selected based on their growth rate, morphology, and identified as strains of KGE1, KGE3, KGE4, and KGE7. The dry biomass of microalgae species ranged between 1 and 2 g L-1 after 21 days of cultivation. The growth kinetics of microalgae was well described by logistic growth model. Among these, KGE7 has the highest biomass production (2.05 +/- 0.35 g L-1), lipid productivity (0.82 +/- 0.14 g L-1), and C16-C18 fatty acid contents (97.6 %). These results suggest that Scenedesmus sp. KGE 7 can be utilized for biodiesel production based on its high biomass and lipid productivity.
Keywords: MUNICIPAL WASTE-WATER; LIPID PRODUCTION; FATTY-ACID; ACCUMULATION; CULTIVATION; GROWTH; REMOVAL; FLOW; CULTURES; BIOMASS